Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To determine the values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex] such that the equations
[tex]\[ 2x + 3y = 7 \][/tex]
and
[tex]\[ 2ax + (a + b)y = 28 \][/tex]
represent coincident lines, we need to have these equations proportional to each other. This means that each corresponding coefficient of the first equation must be a multiple of the corresponding coefficient in the second equation, all by the same factor [tex]\( k \)[/tex].
Let's consider the general form of the equations with the factor [tex]\( k \)[/tex]:
1. The first equation is:
[tex]\[ 2x + 3y = 7 \][/tex]
2. The second equation, when written as a line that is coincident with the first, must be of the form:
[tex]\[ 2k \cdot x + 3k \cdot y = 7k \][/tex]
Given the second equation's form:
[tex]\[ 2ax + (a + b)y = 28 \][/tex]
we equate the coefficients of [tex]\( x \)[/tex], [tex]\( y \)[/tex], and the constants term by term to find [tex]\( k \)[/tex], [tex]\( a \)[/tex], and [tex]\( b \)[/tex].
First, by equating the constants on the right-hand side, we get:
[tex]\[ 28 = 7k \][/tex]
Solving for [tex]\( k \)[/tex]:
[tex]\[ k = \frac{28}{7} = 4 \][/tex]
Now, equate the coefficient of [tex]\( x \)[/tex]:
[tex]\[ 2a = 2k \][/tex]
[tex]\[ 2a = 2 \cdot 4 \][/tex]
[tex]\[ 2a = 8 \][/tex]
[tex]\[ a = \frac{8}{2} = 4 \][/tex]
Next, equate the coefficient of [tex]\( y \)[/tex]:
[tex]\[ a + b = 3k \][/tex]
[tex]\[ 4 + b = 3 \cdot 4 \][/tex]
[tex]\[ 4 + b = 12 \][/tex]
[tex]\[ b = 12 - 4 \][/tex]
[tex]\[ b = 8 \][/tex]
Thus, we have:
[tex]\[ a = 4 \][/tex]
[tex]\[ b = 8 \][/tex]
The sum [tex]\( a + b \)[/tex] is therefore:
[tex]\[ a + b = 4 + 8 = 12 \][/tex]
So, the value of [tex]\( a + b \)[/tex] is:
[tex]\[ \boxed{12} \][/tex]
[tex]\[ 2x + 3y = 7 \][/tex]
and
[tex]\[ 2ax + (a + b)y = 28 \][/tex]
represent coincident lines, we need to have these equations proportional to each other. This means that each corresponding coefficient of the first equation must be a multiple of the corresponding coefficient in the second equation, all by the same factor [tex]\( k \)[/tex].
Let's consider the general form of the equations with the factor [tex]\( k \)[/tex]:
1. The first equation is:
[tex]\[ 2x + 3y = 7 \][/tex]
2. The second equation, when written as a line that is coincident with the first, must be of the form:
[tex]\[ 2k \cdot x + 3k \cdot y = 7k \][/tex]
Given the second equation's form:
[tex]\[ 2ax + (a + b)y = 28 \][/tex]
we equate the coefficients of [tex]\( x \)[/tex], [tex]\( y \)[/tex], and the constants term by term to find [tex]\( k \)[/tex], [tex]\( a \)[/tex], and [tex]\( b \)[/tex].
First, by equating the constants on the right-hand side, we get:
[tex]\[ 28 = 7k \][/tex]
Solving for [tex]\( k \)[/tex]:
[tex]\[ k = \frac{28}{7} = 4 \][/tex]
Now, equate the coefficient of [tex]\( x \)[/tex]:
[tex]\[ 2a = 2k \][/tex]
[tex]\[ 2a = 2 \cdot 4 \][/tex]
[tex]\[ 2a = 8 \][/tex]
[tex]\[ a = \frac{8}{2} = 4 \][/tex]
Next, equate the coefficient of [tex]\( y \)[/tex]:
[tex]\[ a + b = 3k \][/tex]
[tex]\[ 4 + b = 3 \cdot 4 \][/tex]
[tex]\[ 4 + b = 12 \][/tex]
[tex]\[ b = 12 - 4 \][/tex]
[tex]\[ b = 8 \][/tex]
Thus, we have:
[tex]\[ a = 4 \][/tex]
[tex]\[ b = 8 \][/tex]
The sum [tex]\( a + b \)[/tex] is therefore:
[tex]\[ a + b = 4 + 8 = 12 \][/tex]
So, the value of [tex]\( a + b \)[/tex] is:
[tex]\[ \boxed{12} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.